Fluidization treatment material and method for producing fluidization treatment material
By using modified concrete powder and fine aggregate produced through carbon dioxide reaction with recycled materials, the method addresses the instability of compression strength and high emissions in cement-based recycling, achieving enhanced performance and environmental benefits.
Patent Information
- Application Number
- JP2023120305
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-24
- Publication Date
- 2025-02-05
AI Technical Summary
Existing methods for recycling concrete waste in cement-based solidification materials face challenges in achieving stable compression strength and efficient carbon dioxide fixation, leading to high carbon dioxide emissions and inefficient use of recycled materials.
The use of modified concrete powder and modified fine aggregate, produced by reacting recycled concrete powder and fine aggregate with carbon dioxide, to create a fluidization processing material that enhances compression strength and fixes carbon dioxide, reducing the need for traditional cement and lowering emissions.
The solution provides a fluidization processing material with improved compression strength and effective carbon dioxide fixation, allowing for reduced cement usage and decreased atmospheric carbon dioxide emissions while maintaining construction integrity.
Smart Images

Figure 2025017261000003 
Figure 2025017261000004 
Figure 2025017261000005
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a fluidized treatment material and a method for producing the fluidized treatment material. [Background technology]
[0002] Fluidized treated materials are used for backfilling and backfilling of foundations of structures, underground structures, and various urban lifelines. Conventionally, fluidization treatment materials have been used in the form of slurry obtained by dispersing a mixture of mud, waste soil, sludge, and sand (hereinafter also referred to as on-site generated soil) generated at construction sites, etc., with a cement-based or lime-based solidification material added, in water. One mode of use is the soil backfilling filling method, in which the slurry prepared by adding water and a solidification material to on-site generated soil generated at construction sites, etc., mixing and stirring is then performed, and the slurry is then injected into the site to backfill the site. From the viewpoint of effective utilization of waste, a technology has been proposed in which waste is mixed with incineration ash, molten slag, and other waste materials to produce fluidized treatment materials, thereby recycling the waste. Cement, a typical component of solidification agents in fluidization treatment materials, emits a large amount of carbon dioxide due to its raw materials and firing process for cement production, so there is a demand for reducing carbon dioxide emissions. One method is to use demolished concrete generated during the demolition of a structure as a concrete raw material. Fluidized materials obtained using cement as a solidification agent exhibit a desired strength by mixing and stirring an appropriate amount of cement as a solidification agent during production and hardening over time. However, simply reducing the amount of cement used can result in a decrease in the compressive strength of the resulting solidified material, or the composition of the soil generated on-site can fluctuate, resulting in an unstable compressive strength of the solidified material. In recent years, various uses of demolished concrete for the construction of buildings have been investigated, but there has been little attention paid to the application of demolished concrete to fluidized treatment materials.
[0003] Patent Document 1 describes a technique for expanding the uses of fine powder (also called recycled fine powder), which is generated as a by-product when producing recycled aggregate from concrete waste, by adding a small amount of the fine powder to cement clinker. Here, it is described that recycled fine powder is preferable from the viewpoint of improving the strength of the cement obtained by carbonating the cement to an advanced level, but the amount added is only about 5% by mass of the cement clinker, which is difficult to say that this is an efficient use of the recycled fine powder.
[0004] Furthermore, Patent Document 2 focuses on fine powder obtained from waste concrete, discloses that the fine powder can be applied to applications according to its carbonation, and proposes a method of recycling it as part of a cement raw material. The method described in Patent Document 2 describes a method of adding a small amount of fine waste concrete powder that is almost free of calcium hydroxide and has progressed carbonation to cement clinker, which is a cement raw material, and claims that it will be possible to expand the recycling of fine waste concrete powder. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2010-254503 A [Patent Document 2] JP 2012-17227 A Summary of the Invention [Problem to be solved by the invention]
[0006] Recycling concrete waste generated by the demolition of concrete structures and other processes into cement is useful for reducing carbon dioxide emissions, but the methods described in Patent Documents 1 and 2 have the problem that they only achieve a small amount of recycling.
[0007] An object of one embodiment of the present disclosure is to provide a fluidized treatment material using waste material obtained from demolished concrete debris, which has good fluidity and uniaxial compressive strength of the solidified material. Another object of the present disclosure is to provide a suitable method for producing a fluidized treatment material. [Means for solving the problem]
[0008] Means for solving the above problem include the following aspects.
[0009] <1> A fluidization treatment material comprising at least one selected from the group consisting of modified concrete powder, which is a reaction product between carbon dioxide gas and recycled concrete powder, and modified fine aggregate, which is a reaction product between carbon dioxide gas and recycled concrete fine aggregate, a solidification material, and water. In the first aspect, since carbon dioxide is fixed in the modified concrete powder and modified fine aggregate, the fluidity is good and the compressive strength of the solidified material is improved compared to conventional fluidization treatment materials using waste concrete. As a secondary effect, it is effective for recycling waste concrete, as the content of solidifying agent can be reduced, and further, by including at least one of modified powder and modified fine aggregate in which carbon dioxide gas has been immobilized in the fluidization treatment material, carbon dioxide gas can be immobilized in the fluidization treatment material.
[0010] <2> The modified concrete powder and the modified fine aggregate are contained in a ratio of 9:1 to 5:5 by mass. <1> The fluidized treatment material described in the above. In the second aspect, the applications of recycled powder, which has been difficult to recycle among conventional concrete waste materials, are expanded, and the compressive strength of the fluidized treatment material is further improved.
[0011] <3> The content of the solidification material is 3.9% to 9.2% by mass based on the total solid content of the fluidization treatment material. <1> or <2> The fluidized treatment material described in the above. In the third aspect, sufficient compressive strength of the solidified material is achieved even if the content of the solidification material is kept low compared to conventional fluidization treatment materials. Therefore, the content of cement, which is a typical solidification material, can be reduced, and the generation of carbon dioxide gas during cement production can be suppressed.
[0012] <4> A method for producing a fluidized treatment material comprising the steps of: Step I of crushing demolished concrete debris and separating it into fine powder having a maximum particle size of 1.2 mm or less, fine aggregate, and coarse aggregate; Step II of contacting the fine powder and the fine aggregate obtained in Step I with carbon dioxide gas, respectively, to obtain a modified concrete powder in which the carbon dioxide gas has been immobilized, and a modified fine aggregate in which the carbon dioxide gas has been immobilized; and Step III of mixing at least one selected from the group consisting of the modified concrete powder and modified fine aggregate obtained, with a solidification agent and water to obtain a fluidized treatment material. In the fourth aspect, a fluidized treatment material having good fluidity and capable of providing a solidified product with sufficient compressive strength even when the content of the solidifying material is reduced can be suitably produced. In addition, by fixing carbon dioxide gas in the recycled powder and recycled fine aggregate obtained from demolished concrete debris during production to obtain modified powder and modified fine aggregate, carbon dioxide gas can be fixed in the fluidized treatment material, and carbon dioxide emissions into the atmosphere can be suppressed. Effect of the Invention
[0013] According to one embodiment of the present disclosure, a fluidized treatment material having good fluidity and uniaxial compressive strength of the solidified product can be provided by using waste material obtained from demolished concrete rubble. According to another embodiment of the present disclosure, a suitable method for producing a fluidized treatment material can be provided. [Brief description of the drawings]
[0014] [Figure 1] FIG. 1 is a graph showing the unconfined compressive strength of solidified materials of the fluidized treatment materials of Example 2 and Comparative Example 1 from an age of 1 day to an age of 90 days. [Diagram 2] FIG. 2 is a graph showing the pH values of the fluidization treatment materials of Example 2 and Comparative Example 1 from day 1 to day 6 of age. [Diagram 3] FIG. 3 is a graph showing the unconfined compressive strength of the solidified material of the fluidized treatment material of Example 3 from an age of 1 day to an age of 90 days. [Figure 4] FIG. 4 is a graph showing the unconfined compressive strength of the solidified materials of the fluidized treatment materials of Example 5 and Comparative Example 3 from an age of 1 day to an age of 90 days. [Diagram 5] FIG. 5 is a graph showing the pH values of the fluidization treatment materials of Example 5 and Comparative Example 5 from 1 day to 6 days of age. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] The contents of the present disclosure will be described in detail below. These descriptions and examples are illustrative of the embodiments in the present disclosure and are not intended to limit the scope of the embodiments. In the present disclosure, a numerical range indicated using "~" indicates a range that includes the numerical values before and after "~" as the minimum and maximum values, respectively. In the numerical ranges described in the present disclosure in stages, the upper or lower limit value described in one numerical range may be replaced with the upper or lower limit value of another numerical range described in stages. In addition, in the numerical ranges described in the present disclosure, the upper or lower limit value of the numerical range may be replaced with a value shown in the examples. In the present disclosure, combinations of two or more preferred embodiments are more preferred embodiments.
[0016] In the present disclosure, the term "total solid content" refers to the total mass of the components excluding the solvent from the entire composition of the composition. Also, as described above, the term "solid content" refers to the components excluding the solvent, and the components may be solid or liquid at, for example, 25°C. "Room temperature" refers to an ambient temperature that is not specifically temperature controlled, and in this disclosure refers to "25°C" unless otherwise specified.
[0017] In this disclosure, fine powder obtained by crushing and classifying demolished concrete debris is referred to as recycled concrete powder, and fine aggregate obtained by crushing and classifying demolished concrete debris is referred to as recycled fine aggregate. In addition, the reaction product of recycled concrete powder and carbon dioxide gas is called modified concrete powder (modified powder), and the reaction product of recycled concrete fine aggregate and carbon dioxide gas is called modified fine aggregate.
[0018] <Fluidization treatment material> The fluidization treatment material disclosed herein contains at least one selected from the group consisting of modified concrete powder, which is a reaction product of carbon dioxide gas and recycled concrete powder, and modified fine aggregate, which is a reaction product of carbon dioxide gas and recycled concrete fine aggregate, a solidification material, and water.
[0019] In the present disclosure, the "fluidization treatment material" is a composition containing at least one type of particle selected from the group consisting of modified concrete powder and modified fine aggregate, a solidification material, and water. The fluidization treatment material is used in the form of a slurry by stirring and mixing the components contained in the composition. The fluidization treatment material can be used in the form of a slurry by injecting it into an opening at a construction site after a pile has been pulled out, or by injecting it into a backfill site after the construction of a lifeline or the like is completed. The injected slurry-like fluidization treatment material hardens, providing the desired reinforcement at the backfill site, etc. Usually, fluidized treatment materials are made by adding solidifying material and water to on-site generated soil to make a slurry, but as mentioned above, on-site generated soil has an inconsistent composition and contains soil particles of various sizes, so it has low fluidity and is not stable in quality. If a large amount of water is added to ensure fluidity, there is a problem that it takes a long time for the soil to harden. In addition, if the content of solidifying material is increased in order to improve the compressive strength of the obtained solidified material, problems such as a decrease in the effect of suppressing carbon dioxide generation arise.
[0020] The fluidization treatment material disclosed herein contains at least one material selected from the group consisting of modified concrete powder, which is a reaction product of carbon dioxide gas and recycled concrete powder, and modified fine aggregate, which is a reaction product of carbon dioxide gas and recycled concrete fine aggregate. In both the modified powder and the modified fine aggregate, the alkalinity is mitigated by fixing carbon dioxide gas. The modified powder becomes a hard and highly brittle powder or particles due to carbonation. For this reason, when the fluidized treatment material is prepared, the particles are decomposed and atomized due to their brittleness when stirred and mixed with the solidification material and water, resulting in better than good fluidity, which is maintained for a certain period of time even after the slurry is prepared. The modified fine aggregate fixes carbon dioxide gas, reducing the water absorption rate and improving the bone dry density, improving dispersibility in the slurry and suppressing the decrease in fluidity caused by the aggregation of fine aggregates.
[0021] Below, each component contained in the fluidization treatment material of the present disclosure will be explained. (Modified powder) The fluidization treatment material of the present disclosure includes modified concrete powder (modified powder) which is a reaction product of carbon dioxide gas and recycled concrete powder. The modified powder is a reaction product of carbon dioxide gas and recycled concrete powder. Generally, recycled concrete powder generated during the demolition and crushing of concrete contains crushed hardened cement powder, as well as ground aggregate powder and crushed sand powder.
[0022] Recycled concrete powder and other products contain calcium derived from cement components in the form of calcium oxide (CaO), calcium hydroxide (Ca(OH)2), etc. The modified powder used in the fluidization treatment material of the present disclosure is not particularly limited, and a reaction product of recycled concrete powder and carbon dioxide gas is used. The modified powder is a powder obtained by efficiently adsorbing carbon dioxide gas to calcium derived from the cement component in the recycled concrete powder by various methods, and it is preferable that the modified powder has more carbon dioxide gas fixed therein than when the recycled concrete powder is left to stand. By adsorbing a large amount of carbon dioxide gas, the compressive strength of the solidified product described below and the carbon dioxide gas fixation efficiency are improved. By absorbing carbon dioxide into recycled concrete powder to obtain a reaction product, a large amount of carbon dioxide can be bound to the calcium, more calcium carbonate (CaCO3) is produced, and more carbon dioxide can be fixed. The reaction between the carbon dioxide gas and the regenerating powder may be carried out in either a dry or wet manner, as described in the production method described later.
[0023] The modified powder contained in the fluidized treatment material of the present disclosure preferably has a carbon dioxide fixation amount of 20 kg or more per 1000 kg of the modified powder, more preferably 25 kg or more, and even more preferably 30 kg or more. By setting the amount of carbon dioxide gas adsorption contained in the modified powder to 20 kg or more per 1,000 kg of the powder, the fluidized treatment material of the present disclosure can fix a large amount of carbon dioxide within its structure, thereby further reducing the burden on the environment.
[0024] The amount of carbon dioxide fixed in the modified powder can be determined from the mass loss at 600° C. to 800° C. in a TG-DTA test (Thermogrammetry-Differential Thermal Analysis). As a TG-DTA measuring device, for example, Thermoplus EVO2 TG-DTA8122 manufactured by Rigaku Corporation can be used. Here, the amount of calcium carbonate contained in the modified powder is measured, and the amount of carbon dioxide gas is calculated from the amount of calcium carbonate contained in the modified powder, and this is regarded as the fixed amount of carbon dioxide gas (carbon dioxide content) in the modified powder.
[0025] There are no particular limitations on the size of the modified powder, so long as it can pass through a sieve with 1.2 mm openings. For example, if the powder is obtained by crushing recycled concrete debris and can pass through a 1.2 mm sieve, that is, the maximum particle size is 1.2 mm or less, there are no particular limitations on the particle size distribution due to differences in crushing method, etc. From the viewpoint of the balance between the amount of carbon dioxide fixed and the strength of the obtained ground improvement product, the average particle size of the modified powder is preferably 1000 μm or less, and more preferably 100 μm or less. By using the modified powder as a fluidization treatment material, it is possible to reduce the amount of fine powder used in preparing the fluidization treatment material, such as on-site generated soil and powder derived from new concrete, and it is further believed that the use of the modified powder can reduce carbon dioxide emissions.
[0026] (Modified fine aggregate) The fluidization treatment material of the present disclosure includes modified fine aggregate, which is a reaction product of carbon dioxide gas and recycled fine aggregate separated from demolished concrete debris. Recycled fine aggregate contains small amounts of concrete-derived components on its surface. By reacting the recycled fine aggregate with carbon dioxide, the carbon dioxide is fixed in the recycled fine aggregate, resulting in a modified fine aggregate containing calcium carbonate. The reaction between the carbon dioxide gas and the recycled fine aggregate may be carried out in either a dry or wet manner, as described later in the production method. In the modified fine aggregate, the cement-derived components in the recycled fine aggregate react with carbon dioxide during the reaction, immobilizing the carbon dioxide in the fine aggregate. As a result, the water absorption rate is lower and the bone dry density is higher than that of recycled aggregate that has not reacted with carbon dioxide. From the viewpoint of the carbon dioxide gas fixation ability of the fluidization treatment material, the amount of carbon dioxide gas adsorbed in the modified fine aggregate is preferably 1 mass% to 20 mass%, and more preferably 3 mass% to 15 mass%, based on the total mass of the modified fine aggregate. The amount of fixed carbon dioxide gas in the modified fine aggregate can be measured by the above-mentioned TG-DTA test.
[0027] (Content ratio of modified powder and modified fine aggregate) The fluidized treatment material of the present disclosure contains at least one selected from the group consisting of modified powder and modified fine aggregate. The content ratio of the modified powder and the modified fine aggregate is arbitrary, and the fluidized treatment material of the present disclosure may contain only the modified powder, or may contain both the modified powder and the modified fine aggregate. The fluidization treatment material of the present disclosure can contain the modified concrete powder and the modified fine aggregate in a ratio of 9:1 to 5:5 by mass. The content ratio of the modified concrete powder to the modified fine aggregate can be less than 10:more than 0 by mass, preferably 9:1 to 3:7, and more preferably 9:1 to 5:5.
[0028] (Solidification material) The fluidization treatment material of the present disclosure includes a solidification material. As the solidification material, any known hydraulic component can be used without limitation. As the solidification material, cement, specifically, Portland cement, blast furnace cement type B, blast furnace cement type C, cement-based solidification material, etc., which are used in ordinary fluidization treatment materials, can be used, and cement, especially Portland cement, is preferred. The fluidized treatment material disclosed herein contains at least one of the modified powders and modified fine aggregates described above, so that even if the amount of solidification material used in the fluidized treatment material is reduced, the compressive strength of the final solidified product can be maintained within a range that does not cause practical problems. The content of the solidification material is preferably 3.0 mass % to 10.0 mass %, more preferably 3.9 mass % to 9.2 mass %, and even more preferably 4.5 mass % to 9.0 mass %, based on the total solid content of the fluidization treatment material.
[0029] (water) The fluidization treatment material of the present disclosure includes water. There are no particular limitations on the water contained in the fluidization treatment material. When preparing a slurry-like composition that can be mixed with the above-mentioned modified powder and solidifying agent to be injected as a fluidization treatment material, as long as it satisfies conditions such as not containing any harmful substances and not impairing the hardening properties of the binder, tap water, reclaimed water, stored rainwater, etc. may be appropriately selected and included. The water content is appropriately selected depending on the objectives, such as the fluidity required for the fluidization treatment material and the compressive strength of the solidified product. The total content of solids contained in the fluidization treatment material, such as binder and modified powder, relative to the mass of water, i.e., the water / solid ratio, can be 25% to 40%. Note that, for example, when the water / solid ratio is set to less than 25%, preferably 20% or less, for the purpose of improving the compressive strength of the solidified fluidization treatment material, a known chemical admixture may be further included for the purpose of improving fluidity.
[0030] There are no particular limitations on the method of using the fluidization treatment material disclosed herein, and it can be applied to general methods of use, such as soil backfilling and filling methods, and pile extraction hole backfilling methods, and the fluidization treatment material can be made into a slurry and injected for use. The fluidized treatment material disclosed herein contains at least one of modified powder and modified fine aggregate derived from recycled concrete debris, and therefore has good fluidity and good compressive strength of the solidified product, making it suitable for a variety of applications. In addition, since carbon dioxide gas is fixed in the modified powder and modified fine aggregate contained in the fluidized treatment material, the fluidized treatment material has the additional effect of fixing carbon dioxide gas in the backfill material, such as the ground, which is useful for reducing carbon dioxide gas in the atmosphere.
[0031] There are no particular limitations on the method for producing the fluidized treatment material of the present disclosure, but from the standpoint of effectiveness, it is preferable to produce it by the method for producing the fluidized treatment material of the present disclosure described below.
[0032] <Method of manufacturing fluidized treatment material> The manufacturing method of the fluidized treatment material disclosed herein (hereinafter also referred to as the manufacturing method disclosed herein) includes step I of crushing demolished concrete debris and separating it into fine powder having a maximum particle size of 1.2 mm or less, fine aggregate, and coarse aggregate, step II of contacting the fine powder and the fine aggregate obtained in step I with carbon dioxide gas, respectively, to obtain a modified concrete powder in which the carbon dioxide gas is immobilized and a modified fine aggregate in which the carbon dioxide gas is immobilized, and step III of mixing at least one selected from the group consisting of the modified concrete powder and modified fine aggregate obtained, with a solidification agent and water to obtain a fluidized treatment material.
[0033] (Process I) In step I, the demolished concrete debris is crushed and separated into fine powder with a maximum particle size of 1.2 mm or less, fine aggregate, and coarse aggregate. There is no particular limitation on the method for crushing or grinding the demolished concrete debris to obtain recycled powder and recycled fine aggregate, and any known crushing or grinding device can be used. Multi-stage crushing may be performed in which the demolished concrete is first coarsely crushed and the obtained coarsely crushed material is further crushed or ground. For coarse crushing of the demolished concrete debris, a known crusher such as a jaw crusher or an impeller breaker can be used. When the coarsely pulverized material is further subjected to crushing or the like, for example, a crushing device of the blast shot type, an impact crusher, or a grinding device of the mechanical rubbing type without heating can be used.
[0034] Demolished concrete debris is crushed or ground to obtain concrete chunks with a particle size of 40 mm or less, which are then further crushed or ground, and the crushed material is then classified by particle size to obtain recycled coarse aggregate and recycled fine aggregate. Methods for further crushing concrete blocks with a particle size of 40 mm or less include crushing using a crusher such as a jaw crusher or impeller breaker, using a mechanical grinding method without heating, using a heated grinding method, and the blast shot method. From the viewpoint of lower energy consumption, crushing using a crusher, the mechanical grinding method without heating, and the blast shot method are preferred.
[0035] After separating the recycled coarse aggregate, a mixture of recycled fine aggregate with a particle size of less than 5 mm and recycled concrete fine powder with a particle size of 1.2 mm or less is obtained. Recycled fine aggregate can be obtained by separating fine powder with a particle size of 1.2 mm or less from fine particles with a particle size of less than 5 mm obtained after classifying recycled coarse aggregate. Separation of fine powder can be performed by known methods such as sieving, air classification, etc.
[0036] (Process II) Step II is a step in which the recycled powder and recycled fine aggregate obtained in Step I are contacted with carbon dioxide gas to obtain modified concrete powder in which the carbon dioxide gas has been immobilized and modified fine aggregate in which the carbon dioxide gas has been immobilized.
[0037] At least one of the recycled powder and the recycled fine aggregate is reacted with carbon dioxide gas to obtain at least one of the modified powder and the modified fine aggregate as a reaction product. In the following, either or both of the recycled powder and the recycled fine aggregate may be collectively referred to as "recycled powder, etc." The reaction between the regenerated powder and carbon dioxide may be a dry method or a wet method. The dry method includes a method in which the regenerated powder is placed in a closed space and contacted with carbon dioxide at a concentration of 5% or more in an atmosphere at a temperature of 5°C to 200°C. As the wet method, for example, a method in which the regenerated powder or the like is immersed in water and carbon dioxide gas is supplied to the water until the pH of the water reaches 6 to 8 can be mentioned.
[0038] (Reaction of recycled powder with carbon dioxide: dry method) When modifying regenerated powder, etc., using a dry method, the regenerated powder, etc. can be placed in a closed space, and the closed space can be filled with carbon dioxide gas with a concentration of 5% or more to contact the regenerated powder, etc., to obtain the modified powder, etc.
[0039] In addition, carbon dioxide gas separated and recovered in a factory or the like can also be used as carbon dioxide gas for the reaction. By using exhaust gas containing carbon dioxide, recovered carbon dioxide, etc. for the carbon dioxide fixation treatment, it is possible to simultaneously reduce the carbon dioxide in the exhaust gas and modify the regenerated powder, etc. by adsorbing the carbon dioxide to the regenerated powder, etc. When the temperature of the exhaust gas is high, exceeding 100°C, efficient carbon dioxide fixation treatment can be performed without particularly heating the closed space, and there is also the advantage that reduction in energy consumption and reduction in carbon dioxide in the exhaust gas can be achieved at the same time. For the purpose of efficiently carbonating the regenerated powder, etc., the closed space may be pressurized and carbon dioxide gas may be supplied to contact the regenerated powder, etc. The treatment by the dry method can also be carried out using a commercially available neutralization accelerator (for example, a high-concentration neutralization accelerator test device manufactured by Marui Co., Ltd.).
[0040] The preferred treatment time in the dry method is appropriately selected in relation to the carbon dioxide gas concentration and supply amount. For example, when carbon dioxide gas with a concentration of 10% to 50% is used, the treatment time can be 1 hour or more, preferably 24 hours or more, more preferably 2 days or more, even more preferably 5 days or more, and even more preferably 10 days or more. There is no particular upper limit to the treatment time, but from the viewpoint of production efficiency, it can be 20 days or less. The preferred treatment time can be appropriately selected depending on the state of the recycled powder, etc., and the physical properties of the required modified powder, etc. For example, in the case of focusing on recycled fine aggregate, when the amount of cement component adhering to the recycled fine aggregate is small, and when the carbon dioxide gas fixation treatment is performed only on the cement powder adhering to the surface of the recycled fine aggregate and its vicinity, the treatment time can be 1 to 2 hours to obtain the desired modified fine aggregate. When the treatment time in the dry method is 5 days or more, it is preferable to stir the regenerated powder, etc., left in the closed space once every several hours to 3 days from the viewpoint of making the carbonation progress more efficiently. Stirring allows the contact between the regenerated powder, etc. and the carbon dioxide gas to occur more uniformly, and it is possible to reduce unreacted regions, such as parts of the regenerated powder, etc., or parts of individual regenerated powder, etc. that are not carbonated.
[0041] (Reaction of recycled powder with carbon dioxide: wet method) The wet method can be carried out by immersing the regenerated powder obtained in step I in water and supplying carbon dioxide gas to the water until the pH of the water reaches 6 to 8, preferably 6.8 to 8.0, and more preferably about 6.8 to 7.0. A specific example of the wet method is to immerse the regenerated powder in water by filling a container containing the regenerated powder with water and then bubbling the water with carbon dioxide gas. By immersing the regenerated powder in water, the pH of the immersion liquid may become about 10 to 12. For example, when using regenerated powder, a method can be used in which the regenerated powder is mixed with water to prepare a slurry, which is then allowed to stand as is for 30 to 90 minutes to allow the powder to blend, and carbon dioxide gas is then supplied to the slurry.
[0042] There is no particular limitation on the water used for immersion. From the viewpoint of treatment efficiency, it is preferable that the water used contains a small amount of impurities that form salts upon contact with carbon dioxide gas, and examples of the water that can be used include tap water, industrial water, and ion-exchanged water.
[0043] When the wet method is carried out, the carbon dioxide gas concentration supplied to the water can be 5%, preferably 10% or more, and more preferably 20% or more. There is no particular upper limit to the carbon dioxide gas concentration, and the carbon dioxide gas concentration may be 100%. The higher the carbon dioxide concentration, the more efficient the carbon dioxide fixation process of the regenerated powder, etc. tends to be. The carbon dioxide gas to be supplied may be exhaust gas containing carbon dioxide gas, recovered carbon dioxide gas, etc., as in the dry method. When exhaust gas, etc. is used as a carbon dioxide gas supply source, the carbon dioxide gas concentration depends on the amount of carbon dioxide gas contained in the exhaust gas. Even when exhaust gas is used, the carbon dioxide gas concentration in the exhaust gas is preferably 5% or more.
[0044] The amount of carbon dioxide gas supplied to the water in which the regenerated powder is soaked is set at a supply rate of 1 m 3 / hr~100m 3 By blowing in carbon dioxide gas at the above-mentioned supply rate, the regenerated powder, etc. immersed in water is sufficiently contacted with the carbon dioxide gas, carbonation of the regenerated powder, etc. progresses, and modified powder, etc. is obtained.
[0045] The amount of carbon dioxide gas supplied to the water in which the regenerated powder etc. is soaked and the supply rate of carbon dioxide gas at the above concentration can be appropriately selected depending on the purpose. By blowing carbon dioxide gas with the supply amount (total amount) and supply rate of carbon dioxide gas optimized, the contact between the regenerated powder etc. soaked in water and the carbon dioxide gas is efficiently carried out, and carbonation of the regenerated powder etc. progresses. In addition, the solubility of carbon dioxide in water increases as the water temperature decreases, so there is no need to specifically control the water temperature. When exhaust gas is used as a carbon dioxide supply source, the temperature of the water may rise depending on the temperature of the exhaust gas. However, since the water temperature never reaches 100°C, it is not considered that this will affect the progress of the carbon dioxide fixation process using regenerated powder, etc.
[0046] There is no particular limitation on the temperature of water in the wet treatment, and the treatment can be carried out at room temperature. When exhaust gas is used to supply carbon dioxide, the temperature of the water may rise to, for example, about 90° C. depending on the temperature and supply amount of the exhaust gas, but the carbon dioxide fixation treatment can be carried out even under such temperature conditions.
[0047] There is no particular limitation on the treatment time of the wet treatment, which can be, for example, 5 minutes to 10 hours, and preferably 30 minutes to 6 hours. Since the pH of the water tends to decrease as the carbonation of cement-derived components contained in the recycled powder and recycled fine aggregate progresses due to contact between the recycled powder and carbon dioxide, the end point of the carbon dioxide fixation treatment may be the time when the pH of the water reaches 6 to 8. It is preferable to carry out the wet treatment until the pH of the water reaches 6.5 to 7.0, and it is more preferable to carry out the wet treatment until the pH reaches 6.5 to 6.8. It is even more preferable to continue the wet treatment for an additional 30 to 90 minutes after the pH of the water reaches a target value, for example, the pH of the water reaches 6.5 to 7.0. Furthermore, it is more preferable that once the pH reaches the desired value, the wet treatment is continued for a further 30 to 90 minutes, and then the solution is allowed to stand for a further hour, after which it is confirmed that the change in pH of the water is 0.2 or less, marking this as the end point of the carbon dioxide fixation treatment. This is to confirm that when the recycled fine aggregate is carbonated, the reaction of the hydrates incorporated therein has also been substantially completed. The pH of the water in the wet process can be measured with a known pH meter.
[0048] (Process III) Step III is a step of obtaining a fluidization treatment material by mixing at least one selected from the group consisting of the obtained modified concrete powder and modified fine aggregate with a solidification material and water. The fluidization treatment material is generally prepared in a factory. First, the modified powder obtained in step II and the solidification material are weighed, added to a predetermined amount of water, and thoroughly stirred to obtain a slurry-like fluidization treatment material. The fluidization treatment material of the present disclosure has good fluidity and exhibits pourable fluidity immediately after preparation and even after 60 minutes of aging.
[0049] In step III, when the prepared fluidization treatment material is charged at the site while maintaining its fluidity, the water / solids ratio can be set to 25% to 40%. In addition, when the water / solid ratio is set to less than 25%, preferably 20% or less, for the purpose of improving strength, etc., it is preferable to use a chemical admixture from the viewpoint of improving fluidity. That is, the fluidization treatment material prepared in step III can further contain a chemical admixture.
[0050] The chemical admixture may be selected from known chemical admixtures capable of improving the fluidity of the cement slurry, and examples of the chemical admixture include chemical admixtures containing a water-soluble vinyl copolymer. The content of the chemical admixture is appropriately selected depending on the purpose, and is generally, but not limited to, 0.3 mass % to 1.0 mass % based on the total mass of the binder.
[0051] (Application method for fluidized treatment materials) Next, a method for applying a fluidized treatment material using the mixture obtained by the manufacturing method of the present disclosure will be described below. Hereinafter, an example will be described in which cement is used as a binder. The fluidized treatment material is poured into the space to be backfilled while maintaining its fluidity. The fluidized treatment material obtained by the manufacturing method of the present disclosure has good fluidity and stability over time, and therefore maintains a favorable fluidity for about one hour after preparation, making it suitable for use in various sites.
[0052] The fluidized treatment material disclosed herein has good fluidity and the compressive strength of the solidified material is at a level that does not pose any practical problems, and therefore can be suitably used in any construction method, forming the necessary solidified material and making it suitable for backfilling, etc. According to the manufacturing method of the fluidized treatment material disclosed herein, the content of binder such as cement used in the manufacture of the fluidized treatment material is reduced, and modified powder in which carbon dioxide gas is immobilized is used. As a result, a uniaxial compressive strength is achieved that is sufficient for practical use, the necessary reinforcing effect is obtained, and because it contains a dense modified powder in which carbon dioxide gas is fixed, it is expected that the leakage of harmful substances at construction sites, for example, can be suppressed.
[0053] The fluidized treatment material disclosed herein can be directly applied to any of the construction methods for conventional fluidized treatment materials, and one of the advantages of the manufacturing method disclosed herein is that the solidified material in which carbon dioxide is easily immobilized is immobilized, for example, in the ground, thereby reducing the release of carbon dioxide into the atmosphere. In addition, the use of modified powders derived from recycled concrete debris can also lead to the effective use of waste materials, including concrete.
[0054] (Physical properties of solidified fluidized treatment materials) -Compressive strength- The solidified fluidized treatment material of the present disclosure preferably has a compressive strength that is practically acceptable depending on the purpose. The strength development of the solidified material of the fluidized treatment material is judged by the uniaxial compressive strength of the solidified material measured by the following method. Unconfined compressive strength is measured based on JIS A 1108:2018. The target value of the compressive strength of the ground improvement body disclosed in this disclosure is appropriately selected depending on the purpose of construction. In general, the uniaxial compressive strength of the solidified material at one day of age is 0.1 N / mm2 The unconfined compressive strength of the solidified material after 10 days is 0.2N / mm 2 It is preferable that the compressive strength of the solidified material after 20 days is 0.3 N / mm 2 More preferably, it is equal to or greater than this.
[0055] -pH of fluidized material- Since the fluidized treatment material of the present disclosure contains modified powder in which carbon dioxide gas is immobilized, the alkalinity is reduced compared to when it contains regenerated powder in which carbon dioxide gas is not immobilized. As a guideline, the pH of the fluidized treatment material at one day of age is preferably 12.0 or less. The pH of the fluidized treatment material containing recycled powder, etc., measured at one day of age is approximately 12.35, which is expected to reduce the alkalinity and, for example, reduce the impact of alkalinity on nearby metal components.
[0056] -Liquidity- From the viewpoint of workability, it is preferable that the fluidization treatment material has good fluidity. The fluidity of the fluidized treatment material is measured in terms of flow value in accordance with JIS R 5201. The flow value one hour after the preparation of the fluidized treatment material is preferably 140 mm or more, and more preferably 200 mm or more. Bleeding is evaluated in accordance with the Japan Society of Civil Engineers standard "Test method for fluidity of injection mortar for prepacked concrete (JSCE-F 522-2018)." Bleeding is preferably 1.0% to 3.0% after 24 hours, and more preferably less than 1.0%. EXAMPLES
[0057] The fluidized treatment material and the manufacturing method thereof according to the present disclosure will be described below with reference to examples. It goes without saying that the fluidized treatment material and the manufacturing method thereof according to the present disclosure are not limited to the following examples, and various modifications are included within the scope of the present disclosure.
[0058] <Modified Powder Production Examples 1 and 2> The modified powder was prepared using demolished concrete rubble. Concrete chunks generated during the demolition of buildings were crushed to obtain coarsely crushed material of less than 40 mm, which was then crushed and sieved to obtain powder that passed through a sieve with 1.2 mm openings, and used as recycled concrete powder. (Step I) In this manufacturing example, the recycled concrete powder was obtained by crushing the concrete by collision between samples without using media using a blasting machine. In addition, when strength tests were conducted on concrete cores taken from the floors of each floor of the building before demolition, which is the raw material for recycled concrete debris, the average compressive strength of the cores was 27.4 N / mm 2 It was.
[0059] The obtained recycled concrete powder was contacted with carbon dioxide gas to obtain a carbon dioxide fixation powder. First, a wet carbonation device equipped with a 20 L container was prepared, and water and recycled concrete powder were put into the container and stirred to prepare a slurry with a solid concentration of 125 g / L. After leaving the slurry to stand for 60 minutes, carbon dioxide gas was supplied at 20 L / min, and after the pH of the slurry reached 6.8, the supply of carbon dioxide gas was continued for another 60 minutes, and then the slurry was left to stand, the water was separated, and a carbon dioxide fixation powder was obtained. Since the carbon dioxide fixation powder contains water, the water was further removed by pressing to make the water content about 30%. The powder obtained by (Step II-A) (wet method) may be referred to as "powder (I)" below.
[0060] The same recycled concrete powder was also placed in a tank at 20°C, 60% RH, and 10% carbon dioxide concentration for 9 days. During this time, the recycled concrete powder was stirred every day so that the carbon dioxide would come into contact with the entire recycled concrete powder, and a carbon dioxide fixation powder was obtained. (Step II-B) The powder obtained by Step II-B (dry method) may be referred to as "powder (II)" below.
[0061] (Evaluation of carbon dioxide fixation powder) The physical properties of the carbon dioxide fixation powder obtained through step B-1 (powder (I)) and the carbon dioxide fixation powder obtained through step B-2 (powder (II)) were evaluated by the following methods.
[0062] The 50% particle size of each powder was determined from the particle size distribution using a laser diffraction / scattering particle size distribution analyzer (Microtrac MT3300EXII, manufactured by Microtrac Bell Co., Ltd.). The density of each powder was measured using a gas phase substitution test device (automatic true density measurement device BELPycno, manufactured by Microtrack BEL Co., Ltd.). In the TG-DTA test, the amount of calcium carbonate in each powder was calculated from the mass loss at 600℃ to 800℃ using Thermo plus Evo2 TG-DTA8122 (manufactured by Rigaku Corporation). Furthermore, the amount of carbon dioxide fixed in the powder was calculated from the amount of calcium carbonate. The results are shown in Table 1 below. As a reference example, the results for the recycled concrete powder (powder (0)) obtained in step I, i.e., the recycled powder that had not reacted with carbon dioxide, are also shown.
[0063] [Table 1]
[0064] Furthermore, each powder was analyzed using an X-ray diffractometer (D8 ADVANCE, manufactured by Bruker).
[0065] As a result of the analysis, peaks of hydrates such as ettringite (Ett) and calcium hydroxide (CH) were confirmed in the untreated powder (powder (0)) that had only been subjected to step A, but no hydrate peaks were observed in powder (I) and powder (II). It is considered that the hydrates contained in the powder disappeared due to step II. In addition, the amount of calcium carbonate contained in the powder was increased by about 7% in Powder (I) and Powder (II) compared to Powder (0), and the measurement of the amount of fixed carbon dioxide confirmed that by carrying out Process B, the amount of fixed carbon dioxide in the recycled concrete powder increased by about 30 kg per ton compared to untreated Powder (0).
[0066] From the above results, it can be seen that in the manufacturing method of the ground improvement body disclosed herein, carrying out step II does not significantly affect the particle size and density of the powder, and more carbon dioxide is fixed.
[0067] <Modified fine aggregate manufacturing example 3> The recycled fine aggregate obtained by classification in step II was subjected to a carbon dioxide fixation process in a high-concentration carbonation acceleration test device manufactured by Marui Co., Ltd. The recycled fine aggregate was spread to a thickness of about 2 cm in the above-mentioned device, and left to stand in the device (closed space) set to a carbon dioxide concentration of 10%, a temperature of 20±2°C, and a humidity of 60±5%RH. The mass was measured every 2 to 3 days and the mixture was stirred to make it uniform. This was treated for 7 days to obtain modified fine aggregate.
[0068] <Examples 1 to 5> The modified powder and the modified fine aggregate were used to produce a fluidized treatment material. Tap water was used to produce the fluidized treatment material. (Materials used) -Binding material- Portland cement (Nippon Steel Blast Furnace Cement Co., Ltd., density 3.04g / cm 3 )
[0069] -Modified powder, etc.- Modified powder (I), modified powder (II), and modified fine aggregate (III) obtained in the above manufacturing examples
[0070] The recycled powder, cement (solidification material), and water were mixed in the amounts shown in Table 2 below, and stirred to produce the fluidization treatment materials of Examples 1 to 5. (Step III)
[0071] <Comparative Example 1 to Comparative Example 3> The fluidized treatment materials of Comparative Examples 1 to 3 were manufactured in the same manner as in Examples 1, 3 and 5, except that recycled powder (powder (0)) that had not been subjected to carbon dioxide fixation treatment and recycled fine aggregate (fine aggregate (0)) that had not been subjected to carbon dioxide fixation treatment were used for the modified powder and modified fine aggregate.
[0072] The components prepared according to Table 1 were thoroughly mixed and stirred, and the flow value and bleeding were measured according to the methods described above, and evaluated according to the following evaluation criteria.
[0073] (Flow value) A: Over 200mm B: 140mm~200mm C: Over 100mm and under 140mm D: Less than 100mm Grades A to C are levels that are problem-free in practical use, and grades A and B are preferable levels.
[0074] (Breeding) A: Less than 1.0% B: 1% to 3.0% C: More than 3.0% and less than 5.0% D: More than 5.0% Grades A to C are levels that are problem-free in practical use, and grades A and B are preferable levels.
[0075] (Compressive strength of solidified material) The produced fluidized treatment material slurry was poured into a formwork (size: diameter 50 mm, height 100 mm) and allowed to harden to obtain a solidified material for uniaxial compression tests. The compressive strength was measured using the method described above and evaluated according to the following criteria. -Unconfined compressive strength at 3 days old- A: 0.05N / m 2 Exceed B: 0.03N / m 2 ~0.05N / m 2 C: 0.03N / m 2 less than
[0076] - Uniaxial compressive strength at 7 days old - A: 0.1N / m 2 Exceed B: 0.065N / m 2 ~0.1N / m 2 C: 0.065N / m 2 less than The results are shown in Table 2.
[0077] - Carbon dioxide reduction effect - The carbon dioxide reduction effect was calculated by subtracting the carbon dioxide fixed in the ground improvement body from the carbon dioxide generated during the production of cement used in constructing each ground improvement body. Carbon dioxide emissions resulting from the energy used in transporting materials and constructing the ground improvement body were not taken into account. The carbon dioxide generated during cement production was calculated using the value of 451.8 kg-CO2 / t for blast-furnace cement type B in the appendix on page 8 of the Cement Association: Summary of Cement LCI Data (February 2023). (See https: / / www.jcassoc.or.jp / cement / 4pdf / jg1i_01.pdf) The amount of carbon dioxide fixed in the ground improvement material was calculated assuming that the amount of CO2 fixed by the fine powder per 1,000 kg is 90 kg-CO2 / t. This is shown in Table 2 as "CO2 reduction effect."
[0078] [Table 2]
[0079] The fluidized materials of Examples 1 to 5, which contained at least one of the modified powder (I) and the modified fine aggregate, had good fluidity. In addition, the initial uniaxial compressive strength of the solidified materials of the fluidized materials of Examples 2 to 5, i.e., at 1 day and 3 days, was at a practically acceptable level. The fluidized material of Example 1 has a low solidification material content and the initial unconfined compressive strength is somewhat low. However, as shown in the graph of Example 5 described later, the unconfined compressive strength improves over time, and the unconfined compressive strength at 90 days is 0.18 N / m 2 This reached a level that was practically problem-free. Furthermore, the fluidization treatment materials of Examples 1 to 5, which contain modified powder with carbon dioxide gas immobilized therein, were found to have the effect of reducing the amount of carbon dioxide gas released into the atmosphere.
[0080] <Comparison between Example 2 and Comparative Example 1> A fluidized treatment material of Comparative Example 1 was prepared in the same manner as in Example 1, except that the powder (I) in which carbon dioxide gas was immobilized was replaced by powder (0) in which carbon dioxide gas was not immobilized, to obtain a fluidized treatment material of Comparative Example 1. For the fluidized materials of Example 2 and Comparative Example 1, the unconfined compressive strength of the solidified materials at ages of 1 day and 7 days was measured using the same measurement method as in Example 1. The results are shown in FIG. FIG. 1 is a graph showing the unconfined compressive strength of the solidified fluidized treatment materials of Example 1 and Comparative Example 1 at ages of 1 day to 90 days. In addition, the pH of the fluidization treatment materials of Example 1 and Comparative Example 1 was measured from age 1 to age 6. The results are shown in FIG. FIG. 2 is a graph showing the change in pH of the fluidization treatment materials of Example 1 and Comparative Example 1 from 1 day to 6 days of age. It can be seen from Figure 1 that the solidified product of the fluidized treatment material of Example 1, which uses modified powder (powder (I)), exhibits higher uniaxial compressive strength than the fluidized treatment material of Comparative Example 1, which uses powder (0) in which carbon dioxide gas is not immobilized. As shown in the graph in Figure 1, Comparative Example 1 also receives an A rating for initial uniaxial compressive strength, but no improvement in uniaxial compressive strength over time is observed as shown in the graph of Example 1, and it is clear that the strength required for a solidified product of fluidized treatment material ultimately does not reach that level. 2, it can be seen that the fluidization treatment material of Example 1, which uses the modified powder (powder (I)), has a milder alkalinity than the fluidization treatment material of Comparative Example 1, which uses powder (0) that does not have carbon dioxide gas immobilized therein. It can also be seen that the fluidization treatment material of Example 1 exhibits sufficient alkalinity to solidify the cement component, which is the solidification material.
[0081] <Comparison between Example 3 and Comparative Example 2> A fluidization treatment material of Comparative Example 2 was obtained in the same manner as in Example 1, except that the powder (0) was used instead of the powder (I) in the fluidization treatment material of Example 3. For the fluidized materials of Example 1 and Comparative Example 1, the unconfined compressive strength of the solidified material from an age of 1 day to an age of 90 days was measured using the same measurement method as in Example 1. The results are shown in Figure 3. Note that in this test, the effect of the solidified material was insufficient for the fluidized material of Comparative Example 2, and the unconfined compressive strength could not be measured, so Figure 3 shows only the graph of Example 3. Therefore, FIG. 3 is a graph showing the unconfined compressive strength of the solidified fluidized treatment material of Example 3 from 1 day to 90 days old. FIG. 3 shows that the fluidized treatment material of Example 3, which uses modified powder (powder (I)), exhibits a higher uniaxial compressive strength in the solidified product than the fluidized treatment material of Comparative Example 2, which uses recycled powder in which carbon dioxide gas is not fixed.
[0082] <Comparison between Example 5 and Comparative Example 3> A fluidized treatment material of Comparative Example 3 was obtained in the same manner as in Example 5, except that recycled powder and recycled fine aggregate in which carbon dioxide gas was not fixed were used instead of the fluidized treatment material of Example 5. For the fluidized treatment materials of Example 5 and Comparative Example 3, the unconfined compressive strength of the solidified materials from an age of 1 day to an age of 90 days was measured using the same measurement method as in Example 1. The results are shown in FIG. FIG. 4 is a graph showing the unconfined compressive strength of the solidified fluidized treatment materials of Example 5 and Comparative Example 3 at ages of 1 day to 90 days. Furthermore, the pH of the fluidized treatment materials of Example 5 and Comparative Example 3 was measured from age 1 to age 6. The results are shown in FIG. FIG. 5 is a graph showing the change in pH of the fluidization treatment materials of Example 5 and Comparative Example 3 from 1 day to 6 days of age. It can be seen from Figure 4 that the solidified product of the fluidized treatment material of Example 5, which used the modified powder (powder (I)) and modified fine aggregate, exhibits a higher uniaxial compressive strength than the fluidized treatment material of Comparative Example 3, which used recycled powder in which carbon dioxide gas was not immobilized and recycled fine aggregate in which carbon dioxide gas was not immobilized. As shown in the graph in Figure 4, the initial uniaxial compressive strength of the solidified product of the fluidized treatment material of Comparative Example 3 was also rated A, but no improvement in uniaxial compressive strength over time was observed, as shown in the graph of the solidified product of the fluidized treatment material of Example 5. 5, it can be seen that the fluidization treatment material of Example 5, which uses modified powder and modified fine aggregate, has a milder alkalinity than the fluidization treatment material of Comparative Example 3, which uses powder (0) in which carbon dioxide gas is not immobilized and recycled fine aggregate in which carbon dioxide gas is not immobilized. It can also be seen that the fluidization treatment material of Example 5 exhibits sufficient alkalinity to solidify the cement component, which is the solidification material.
Claims
1. A fluidization treatment material comprising at least one selected from the group consisting of modified concrete powder, which is a reaction product between carbon dioxide gas and recycled concrete powder, and modified fine aggregate, which is a reaction product between carbon dioxide gas and recycled concrete fine aggregate, a solidification material, and water.
2. The fluidization treatment material according to claim 1, comprising the modified concrete powder and the modified fine aggregate in a ratio of 9:1 to 5:5 by mass.
3. The fluidization treatment material according to claim 1 or 2, wherein the content of the solidification material is 3.9% by mass to 9.2% by mass based on the total solid content of the fluidization treatment material.
4. A process I of crushing demolished concrete debris and separating it into fine powder having a maximum particle diameter of 1.2 mm or less, fine aggregate, and coarse aggregate; Step II of contacting the fine powder and the fine aggregate obtained in step I with carbon dioxide gas to obtain a modified concrete powder in which carbon dioxide gas has been fixed and a modified fine aggregate in which carbon dioxide gas has been fixed; A method for producing a fluidized treatment material, comprising step III of mixing at least one selected from the group consisting of the obtained modified concrete powder and modified fine aggregate with a solidification material and water to obtain a fluidized treatment material.
Citation Information
Patent Citations
Fine powder cement
JP2010254503A
Waste concrete fine powder and method for recovering the same
JP2012017227A